The Effect of LDR Ratio, CAR Ratio and BOPO Ratio on ROA in Conventional Banking on the Indonesia Stock Exchange Period 2015-2020 - Hasanudin, Hasanudin; Awaloedin, Dipa Teruna; Apriyati, Nur (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study aims to analyze the effect of the variables measured by the LDR Ratio, CAR Ratio and BOPO Ratio on ROA of Conventional Banking on the Indonesia Impact Exchange for the 2015-2020 period. This study uses 14 conventional banks on the Indonesia Stock Exchange for the 2015-2020 period. The illustration method used is purposive sampling and 10 industries are obtained. This research uses secondary information in the form of financial statements that meet the criteria, the data obtained from the financial statements are obtained from the Indonesia Stock Exchange which can be accessed through https://www.idx.co.id/id . The analytical procedure used in this study is Linear Regression of panel data using the SPSS 25 program. The results of this study show that LDR and BOPO have a significant effect on ROA, while the CAR ratio has no effect on ROA.